PH response type anti-adhesion antibacterial nanorod coating based on bacteriophage endolysin

By applying pH-responsive anti-adhesion antibacterial nanocolumn coating based on endophage lysins on food contact surfaces, the problem of bacterial cross-contamination between food contact surfaces and fresh agricultural products is solved, and efficient antibacterial and anti-fouling effects are achieved , significantly improves food safety.

CN119387128AInactive Publication Date: 2025-02-07SOUTHWEST UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411512214.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent bacterial cross-contamination between the food contact surface and fresh agricultural products, leading to the outbreak of foodborne diseases.

Method used

Using pH-responsive anti-adhesion antibacterial nanocolumn coating based on endophage lysin, the design of ZnO nanocolumn array and bilayer polymer brush combines the pH responsiveness of endophage lysin to achieve non-release of bacteria. The cycle of sterilization and sterilization removal.

Benefits of technology

The antibacterial coating has been used for a long time and multiple times, with anti-adhesion and pH responsiveness, and can switch the antibacterial state according to the number of bacteria in the environment, significantly reducing bacterial cross-contamination and improving food safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387128A_ABST
    Figure CN119387128A_ABST
Patent Text Reader

Abstract

The invention discloses a pH response type nanorod intelligent antibacterial coating constructed on the surface of stainless steel for the first time. According to the coating, stimuli-responsive polymer polyacrylic acid (PAA) and phage-derived endolysin Lys81 are grafted to a ZnO nano-column, and self-regulation is carried out in response to environmental conditions. In the initial stage of bacterial adhesion, the surface of the nanorod shows remarkable mechanical bactericidal activity, and the bacterial adhesion is effectively inhibited by the super-hydrophilic PAA layer. In a later stage, when many live bacteria and dead bacteria adhere to the surface of the nanorod, the PAA chain disintegrates, exposing the endolysin bottom layer that lyses the damaged bacteria. In addition, along with the increase of the pH value of the environment, the attached dead bacteria can be released once the hydrophilicity of the PAA chain is recovered. The purpose of the present invention is to apply an antibacterial coating to a stainless steel surface used in food processing, thereby improving surface hygiene and preventing cross contamination of fresh agricultural products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial coatings, and in particular relates to a method for preparing a pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin. Background Art

[0002] Contamination and cross-contamination of food by bacterial pathogens are major concerns worldwide. It is estimated that approximately 600 million people are infected with foodborne illnesses each year, resulting in 420,000 deaths. A recent study showed that cross-contamination with microbial hazards accounts for 28.6% of all food safety loss events. In the food industry, cross-contamination often affects food contact surfaces (e.g., conveyor belts, cutting tools, and processing equipment). Therefore, there is a need to develop and research methods to prevent cross-contamination between food contact surfaces and fresh produce.

[0003] The bionic nanopillar structure surface is a mechanical bactericidal surface that simulates the natural nanopillar structure. Unlike traditional antimicrobial agents, this type of antimicrobial surface interacts with bacteria through a physical mechanism, and its action is essentially different from that of antibiotics that inhibit the synthesis of certain important proteins, DNA and RNA of bacteria, making it difficult for bacteria to develop drug resistance. In addition, some surface nanomorphologies will affect the attachment and migration behavior of eukaryotic cells on the surface, and because bacteria and eukaryotic cells are different in size and adhesion mechanism on the nanostructure surface, some nanostructures that can physically kill bacteria have excellent compatibility with eukaryotic cells. This "selective killing" property makes the nanostructure surface have broad application prospects.

[0004] Polyacrylic acid (PAA) is a pH-responsive, safe, non-toxic, low-cost, food-grade polyelectrolyte. At low pH, PAA exhibits a compact (but not completely collapsed) globular conformation. However, as the pH increases, ionization occurs and the polymer swells to a fully solvated open-coil conformation. PAA can be surface-initiated by UV irradiation to control thickness and degree of polymerization through photoinduced free radical polymerization.

[0005] 2-Carboxyethyl acrylate (PCEA) is an important polymer material, belonging to the acrylic ester polymer, a copolymer formed by the polymerization reaction of acrylic acid and 2-carboxylic acid. Its chemical structure contains multiple acrylate units, which makes it have good reactivity and processability. In addition, PCEA has low toxicity and good biocompatibility. The polymer brush surface of PCEA can be prepared by UV-induced photograft polymerization. The unique carboxylic acid groups in the polymer brush are activated by EDC and NHS, which can react with proteins to form an amide.

[0006] Phage endolysins are a class of enzymes encoded by bacteriophages (viruses) that can degrade the peptidoglycan (PG) layer in the bacterial cell wall. However, Gram-negative bacteria are generally more resistant to antimicrobial substances than Gram-positive bacteria because the outer membrane (OM) of Gram-negative bacteria hinders the contact between endolysins and the peptidoglycan layer. In addition, phage-derived endolysins are usually large in size and cannot penetrate the outer membrane, so they can only be used in combination with cytotoxic outer membrane permeabilizers (such as EDTA or chloroform). Therefore, it is particularly important to find a safe and non-toxic application method.

[0007] The present invention uses ZnO nanopillar arrays to design a pH-responsive intelligent antibacterial coating constructed on stainless steel. This coating not only serves as a self-cleaning platform to solve the problem of poor surface life of traditional biomimetic nanopillars, but also uses a pH-responsive outer layer to reversibly expose and cover the inner layer of endolysin. The nanopillars can also help endolysin break through the outer membrane barrier to exert antibacterial properties. This design realizes a cyclic process of non-releasable sterilization and dead bacteria removal. In addition, PAA can serve as a protective layer to prevent the exhaustion of bacteriophage endolysin. An intelligent antibacterial surface with bactericidal release function is constructed through the synergistic effect of different components. Due to the low tolerance of nanopillars and endolysin, this antibacterial coating can reduce bacterial cross-contamination when applied to food contact equipment. Summary of the invention

[0008] The present invention aims to provide a coating based on nanopillars and bacteriophage endolysins with anti-adhesion and antimicrobial properties that can be used for a long time and multiple times to prevent cross contamination between food equipment and fresh agricultural products.

[0009] In order to solve the above technical problems, the present invention also provides a method for preparing a pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin, as follows:

[0010] 1. Preparation of nanopillar arrays: Cut the stainless steel plate into 7×2cm2 size, and then dry it after ultrasonic treatment with acetone, anhydrous ethanol and deionized water for 5 minutes. Dissolve an appropriate amount of zinc acetate in anhydrous ethanol and stir at 60°C for 30 minutes to obtain a uniform transparent solution with a concentration of 5mM. Then immerse the cleaned stainless steel substrate in the above solution for 30 seconds, and use a manual lifting machine to pull it into a film at a speed of 3cm·min-1, and then put it into a muffle furnace at 300°C for annealing for 10 minutes. This step was taken 4 times in the experiment to obtain the seed layer. Then, equimolar amounts of zinc nitrate hexahydrate and hexamethylenetetramine solutions were prepared with deionized water, and the equal volumes were fully mixed to obtain a hydrothermal growth solution with a final concentration of 20 mM. The stainless steel plate loaded with ZnO seed crystals was immersed in the hydrothermal growth solution, hydrothermally grown at 90°C for 4 hours, washed several times with deionized water and anhydrous ethanol, and annealed at 500°C for 30 minutes after drying to remove organic residues, thus obtaining a stainless steel plate sample loaded with ZnO nanoarrays. Afterwards, it was immersed in disinfectant alcohol for sterilization and dried for use.

[0011] 2. Preparation of pH-responsive antibacterial coating: The prepared ZnO substrate was immersed in an ethanol solution of 3-(trimethoxymethylsilyl) methacrylate (TMSPMA) with a volume concentration of 2 vol% at room temperature.

[0012] h, take out the sample and put it into an oven at 80°C for 1h to obtain a zinc oxide nanostructure modified by a silane coupling agent, which is recorded as ZnO-TMSPMA. A zinc oxide nanostructure modified by a silane coupling agent is obtained, which is recorded as ZnO-TMSPMA. A 1wt% ethanol solution of the photoinitiator benzophenone (BP) was prepared, and ZnO-TMSPMA was immersed in the ethanol solution of BP for 30 minutes and then dried in the dark. For the ZnO-BP sample, UV grafting was performed, and the aqueous solution of the monomer (ie, CEA or PAA) was degassed with a nitrogen flow. Subsequently, a CEA monomer solution (20 μL, 5wt%) was added to the ZnO-BP sample, and the sample was then covered with a quartz plate. The sandwich system was exposed to UV light (high-pressure mercury lamp, 300W, main wavelength 365nm) for 30 minutes. ZnO-PCEA was activated in a 2-(N-morpholino)ethanesulfonic acid (MES) solution (pH 5.5) containing 0.4 M EDC and 0.1 M NHS at 4°C for 1 h, and Lysin was subsequently chemically immobilized on the polyCEA brush. For the stratified brush samples, UV-graft polymerization of PAA monomers was performed on ZnO-PCEA following the same procedure. The resulting stratified samples were denoted as ZnO-PCEA-PAA. The ZnO-PCEA-PAA samples were incubated in a 1 mg / mL Lys81 solution for 24 h. The samples were then washed and dried. The peptide-loaded samples were named ZnO-PCEA(lys)-PAA.

[0013] 3. The present invention also provides a method for preparing a pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin, comprising the following steps:

[0014] 1) Evaluate the effect of nanopillar morphology on bactericidal performance. The specific method is as follows: the washed stainless steel plate is pulled into a film in a zinc acetate alcohol solution, annealed four times in a muffle furnace at 300°C to obtain a ZnO seed layer, and then an equimolar amount of zinc nitrate hexahydrate and hexamethylenetetramine solution are prepared with deionized water, and the equal volumes are fully mixed to obtain a hydrothermal growth solution with a final concentration of 20mM. The stainless steel plate loaded with ZnO seed crystals is immersed in the hydrothermal growth solution, hydrothermally grown at 90°C for 2, 4, and 8h, and annealed at 500°C for 30min after drying. SEM is used to visualize the morphology of ZnO nanopillars of different morphologies and Salmonella on the surface of the nanopillars at an accelerating voltage of 10kV, and CLSM is combined to further evaluate the effect of nanopillar morphology on bactericidal performance.

[0015] Preferably, the nanorods grown hydrothermally for 4 hours have the best bactericidal properties.

[0016] 2) Evaluate the effect of different UV irradiation times on the thickness and anti-adhesion properties of the polymer brushes. The specific method is as follows: degas the aqueous solution of the monomer (i.e., CEA or PAA) with a nitrogen flow. Add the CEA monomer solution (20 μL, 5 wt%) to the ZnO-BP sample, and then cover the sample with a quartz plate. Expose the sandwich system to UV light (high-pressure mercury lamp, 300 W, main wavelength 365 nm) for 10, 20, and 30 min. Then, UV graft polymerization of PAA monomer was performed on ZnO-PCEA according to the same procedure, and UV light was irradiated for 10, 20, 30, and 40 minutes. Use SEM to visualize the morphology of ZnO-PCEA and ZnO-PCEA-PAA nanopillars with different illumination times and the morphology of Salmonella on the surface of hybrid nanopillars, and combine CLSM and anti-adhesion experiments to detect the effect of different UV irradiation times on the thickness and anti-adhesion properties of the polymer brushes.

[0017] 4. Compared with the prior art, the present invention has achieved the following technical effects:

[0018] The present invention is based on ZnO nanopillars grown on stainless steel plates, and introduces double-layer polymer brushes and bacteriophage endolysins as additional bactericidal units. This design solves the problem that bionic nanopillars are easily masked by dead bacteria and difficult to use for a long time, while giving them anti-adhesion properties and pH responsiveness, allowing the surface to switch between anti-adhesion, bactericidal and dead bacteria release states according to the number of bacteria in the environment. If this antibacterial coating is applied to stainless steel food contact surfaces, it can effectively reduce cross-contamination of fresh agricultural products during processing, minimize the outbreak of large-scale foodborne diseases, and thus significantly improve human health. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:

[0020] Figure 1 Schematic diagram of the preparation of the antibacterial coating in an embodiment of the present invention;

[0021] Figure 2 This is a diagram showing the application results of the pH-responsive anti-adhesive and antibacterial nanocolumn coating based on endolysin prepared in the present invention in actual samples;

[0022] Figure 3 This is a characterization result diagram of the pH-responsive anti-adhesive and antibacterial nanocolumn coating based on endolysin prepared in the present invention;

[0023] Figure 4 This is a diagram showing the antibacterial and anti-adhesion results of the pH-responsive anti-adhesive and antibacterial nanocolumn coating based on endolysin prepared in the present invention;

[0024] Figure 5 This is a graph showing the pH response characteristics of the pH-responsive anti-adhesion and antibacterial nanocolumn coating based on endolysin prepared in the present invention. DETAILED DESCRIPTION

[0025] The present invention is further described below by means of specific examples so that those skilled in the art can better understand the present invention and implement it, but the examples are not intended to limit the present invention.

[0026] Example 1

[0027] Experimental Materials

[0028] In this example, a total of 1 kind of microorganism was used to test the antibacterial ability of the pH-responsive anti-adhesive and antibacterial nanocolumn coating based on endolysin, and the information of the Salmonella strain used is shown in Table 1.

[0029] Table 1

[0030]

[0031]

[0032] Example 2

[0033] See also Figure 1 , preparing a pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin, comprising the following preparation steps:

[0034] 1) Preparation of nanopillar arrays: Cut the stainless steel plate into 7×2 cm 2The size was ultrasonically treated with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence and then dried for use. An appropriate amount of zinc acetate was dissolved in anhydrous ethanol and stirred at 60°C for 30 minutes to obtain a uniform transparent solution with a concentration of 5 mM. Then, the cleaned stainless steel substrate was immersed in the above solution for 30 seconds and then a manual lift was used to lift the substrate at a speed of 3 cm·min. -1 The film was pulled at a speed of , and then placed in a muffle furnace at 300℃ for annealing for 10min. This step was taken 4 times in the experiment to obtain a seed layer. After that, equimolar amounts of zinc nitrate hexahydrate and hexamethylenetetramine solutions were prepared with deionized water, and the equal volumes were fully mixed to obtain a hydrothermal growth solution with a final concentration of 20mM. The stainless steel plate loaded with ZnO seed crystals was immersed in the hydrothermal growth solution, hydrothermally grown at 90℃ for 4h, washed several times with deionized water and anhydrous ethanol, and annealed at 500℃ for 30min after drying to remove organic residues, thus obtaining a stainless steel plate sample loaded with ZnO nanoarrays. Afterwards, it was immersed in disinfectant alcohol for sterilization and dried for standby use.

[0035] 2) Extraction of bacteriophage endolysin (in order to better illustrate the invention, the present invention uses bacteriophage ZBSTP8 as the experimental object. Technicians in this technical field can choose different materials according to actual conditions, but the equivalent substitutions or changes made are all within the scope of protection of the present invention): Use a kit to extract the DNA of bacteriophage ZBSTP8, query the genome sequence of bacteriophage ZBSTP8 from NCBI (registration number: OR939735.1), and design primers according to the endolysin gene sequence. Use phage DNA as a template and primers for PCR amplification to obtain the endolysin encoding gene fragment. Use Beijing Quanshijin Biological Co., Ltd. The E1Expression Kit was used to construct the recombinant plasmid, and the recombinant plasmid was amplified by PCR and verified by sequencing. The recombinant plasmid with the correct sequencing results was transferred into E. coli BL21 (DE3) pLysS competent cells, and IPTG inducer was added to induce the expression of endolysin. The protein bands were observed by SDS-PAGE electrophoresis, and the protein was purified by Ni-NTA purification system.

[0036] 3) Preparation of pH-responsive antibacterial coating: The previously prepared ZnO substrate was immersed in an ethanol solution of 3-(trimethoxymethylsilyl) methacrylate (TMSPMA) with a volume concentration of 2 vol% at room temperature for 10 h. After taking out the sample, it was placed in an oven at 80°C for 1 h to obtain a silane coupling agent-modified zinc oxide nanostructure, which was recorded as ZnO-TMSPMA. A silane coupling agent-modified zinc oxide nanostructure was obtained, which was recorded as ZnO-TMSPMA. A 1wt% ethanol solution of the photoinitiator benzophenone (BP) was prepared, and ZnO-TMSPMA was immersed in the ethanol solution of BP for 30 min and then dried in the dark. For the ZnO-BP sample, UV grafting was performed, and the aqueous solution of the monomer (i.e., CEA or PAA) was degassed with a nitrogen flow. Subsequently, the CEA monomer solution (20 μL, 5wt%) was added to the ZnO-BP sample, and the sample was covered with a quartz plate. The sandwich system was exposed to UV light (high pressure mercury lamp, 300 W, main wavelength 365 nm) for 30 min. ZnO-PCEA was activated in 2-(N-morpholino)ethanesulfonic acid (MES) solution (pH 5.5) containing 0.4 M EDC and 0.1 M NHS at 4 °C for 1 h, and Lysin was subsequently chemically immobilized on the polyCEA brush. For the layered brush sample, UV graft polymerization of PAA monomers on ZnO-PCEA was performed according to the same procedure. The obtained layered sample was denoted as ZnO-PCEA-PAA. The ZnO-PCEA-PAA sample was incubated in 1 mg / mL Lys81 solution for 24 h. The sample was then washed and dried. The peptide-loaded sample was named ZnO-PCEA(lys)-PAA. .

[0037] In the step 2), primers are designed according to the bacteriophage endolysin gene sequence: F: 5'-ATGGCTATTAGCAAAAACATGAAGGC-3', R: 5'-TCATGCCACAACTCCGCC-3'.

[0038] The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin in this embodiment also includes the following preparation method:

[0039] 4) Endolysin induction expression: Select BL21 (DE3) pLysS containing pEASY-lys81 and inoculate it into 20 mL LB broth containing 100 μg / mL ampicillin (Amp), and culture it at 37°C, 120 r / min for 16 h. Inoculate 1 mL of the above bacterial solution into 99 mL LB (Amp+) solution, and culture it at 37°C, 200 r / min for 3.5 h until the OD of the bacterial solution reaches 6000.4-0.6. Add IPTG inducer to induce expression. Take 1mL of bacterial solution and centrifuge it quickly at 4℃ and 12000r / min for 1min, and resuspend the precipitate with 36μL sterile ultrapure water. Add 4μL 4×SDS-PAGE Loading Buffer, mix well, and boil for 3-5min to prepare protein electrophoresis loading solution.

[0040] In the step 6), the optimal induction concentration of IPTG is 1 mmol / L, and the optimal induction expression conditions are 37° C., 200 r / min, and 4 h.

[0041] Example 3

[0042] In this example, the pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin prepared in Example 2 is actually applied, and the application method is as follows:

[0043] Two samples (lettuce and chicken) were selected and confirmed by traditional plate culture method that the antimicrobial coating would not cause cross contamination. The lettuce and chicken were rinsed with sterile water before use. Then, the samples were cut into squares (1×1 cm) using a UV sterilized kitchen knife. 2 ). Inoculate 1 ml of Salmonella bacterial suspension (about 10 8 CFU / ml), and after inoculation, the samples were dried at room temperature for 1 hour. The lettuce and chicken were then gently washed with 1 ml of PBS to remove loose bacterial cells. Then, cross-contamination studies were performed in two steps: (1) bacterial transfer from inoculated fresh produce to SS, where bacteria were transferred from the contaminated surface of fresh produce to coated or uncoated SS; (2) SS to uninoculated fresh produce, where bacteria were transferred from contaminated SS to the surface of fresh produce. To count the number of bacteria on produce and SS, the samples were placed in 1 ml of PBS, shaken and eluted, and diluted in a gradient. The plate count method was used to evaluate the number of bacteria transferred from the surfaces of SS and uninoculated produce. The experiment was performed in triplicate. The results are shown in Figure 2 .

[0044] from Figure 2As can be seen, the efficacy of ZnO-PCEA(lys)-PAA in preventing cross-contamination of fresh produce. In the first phase, we evaluated the transfer of contaminants from produce to food contact surfaces, and the ZnO-PCEA(lys)-PAA coating significantly reduced the transfer of bacteria from contaminated lettuce to food contact surfaces by more than 2 log units (p<0.05) and significantly reduced the transfer of bacteria from contaminated chicken to food contact surfaces by more than 1.19 logs (p<0.05). In the second phase, the transfer of bacteria from contaminated food contact surfaces (stainless steel sheets after contact in the first phase) to uncontaminated fresh produce was evaluated, and the ZnO-PCEA(lys)-PAA coating significantly reduced the transfer of bacteria from contaminated food contact surfaces to uncontaminated lettuce by about 2 logs (p<0.05) and significantly reduced the transfer of bacteria from contaminated contact surfaces to uncontaminated chicken by about 1.06 logs (p<0.05). The above results indicate that the ZnO-PCEA(lys)-PAA coating on the stainless steel sheet reduced the cross contamination of fresh produce from the contaminated surface to the surface of fresh chicken.

[0045] Example 4

[0046] In this example, the pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin prepared in Example 2 was characterized to evaluate whether the preparation was successful and the stability of the antibacterial coating.

[0047] The morphology of ZnO nanorods and ZnO-PCEA(Lys)-PAA was observed using a Phenom Pro SEM at an accelerating voltage of 10 kV. Attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy was performed using an FTIR spectrometer (Thermo Scientific, USA) in ATR mode. XPS (Thermo Scientific ESCALAB Xi+) was used to characterize the surface element distribution of the samples.

[0048] The chemical stability test involved immersing the samples in phosphate buffered saline (PBS, pH 7.4) for 7 days and analyzing the extracted solution using a F-4700 UV-visible spectrometer.

[0049] The water contact angle was measured using an interfacial dilatometric rheometer (OCA25; Dataphysics, Germany). The drop volume for each measurement was 3 μL, and the final average angle was calculated from at least 3 samples.

[0050] Example 5

[0051] This example, combined with experimental research, further proves that the antibacterial coating has strong antibacterial and anti-adhesion effects.

[0052] 1) Antibacterial test

[0053] Before testing, the modified samples and control stainless steel plates were rinsed with distilled water, sterilized with 75% ethanol, and dried completely. Subsequently, the cleaned samples were incubated in 1 mL of a Salmonella bacterial suspension (~10 8 Cells mL -1 , PBS) for 4 hours. After incubation, the sample was removed from the bacterial suspension and gently washed 3 times with sterile PBS. In order to observe the bacterial morphology on the sample surface, the sample was immersed in 4% paraformaldehyde and fixed for 1 hour, then freeze-dried, sprayed with gold, and then photographed with a scanning electron microscope. The survival rate of bacteria on the sample surface was evaluated using live and dead bacterial staining. A mixture of 30 μL SYTO and propidium iodide (PI) was added dropwise to the sample surface and incubated in a dark environment for 15 minutes. The sample surface was then washed with PBS and then photographed using CLSM. ImageJ software (version 1.46; National Institutes of Health, Bethesda, Maryland) was used.

[0054] The bactericidal properties were further evaluated using the plate method. First, 20 μL of the diluted bacterial suspension was dropped onto the sample surface, followed by covering with a soft polyethylene (PE) film and co-cultured at 37°C for 4 h. Subsequently, elution and culture counting were performed.

[0055] 2) Bacterial adhesion assay

[0056] Immerse the sample in 1 mL of bacterial suspension at 37 °C for 10 s. Subsequently, remove the sample and rinse twice with PBS to wash away unattached bacteria. Perform a 10-fold dilution using PBS. Take 10 μL from each gradient and drop it onto the plate. Then incubate the plate to count adherent bacterial colonies.

[0057] Example 6

[0058] This example, combined with experimental research, further proves that the antibacterial coating has pH response characteristics.

[0059] 1) Under buffer conditions: Coated SSS and uncoated SSS were incubated with 1 mL of bacterial suspension for 4 h, and different pH buffers (1 mL) were added. Then, the samples were shaken and incubated for 1 h in a shaker. Finally, the samples were washed and dried, and the antibacterial properties were determined by CLSM.

[0060] 2) Under nutrient-rich conditions: The samples were incubated with 1 mL of bacterial suspension for 4, 8, and 12 h. The antibacterial properties of the samples were determined using CLSM.

[0061] In summary, the present invention prepares a pH-responsive anti-adhesive antibacterial nanopillar coating based on bacteriophage endolysin through a simple and sustainable method. Compared with ZnO nanopillars alone, the pH-responsive outer layer on the surface of this hybrid nanopillar can adjust the antibacterial behavior as needed. And this nanopillar surface can maintain the bactericidal effect on bacteria for up to 4 days. At the same time, the non-leaching strategy that retains endolysin on the surface to avoid depletion enables the surface to maintain effective bactericidal effects after 4 cycles of use. Utilizing the excellent bactericidal efficiency of ZnO nanopillars and the stimuli-responsive properties of PAA brushes, the patterned surface of ZnO-PCEA(lys)-PAA nanopillars exhibits excellent and sustainable antibacterial ability with a bactericidal rate of more than 99%. The results of this study also demonstrate the potential application of this antibacterial coating on stainless steel food contact surfaces to reduce cross-contamination of fresh agricultural products during processing. Reducing cross-contamination in food production facilities can help minimize the incidence of large-scale foodborne disease outbreaks, thereby significantly improving human health.

[0062] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin, with stainless steel as substrate and hydrothermal growth of nanocolumns, characterized by: A double layer of polymer brushes, polyCEA (PCEA) and polyacrylic acid (PAA), were grafted onto the nanopillars by UV, and endolysin was immobilized on the polyCEA brushes.

2. A pH-responsive anti-adhesive antibacterial nanocolumn coating based on bacteriophage endolysin, the preparation method of which comprises the following steps: 1) Preparation of nanopillar arrays: Cut the stainless steel plate into 7×2 cm 2 The size was ultrasonically treated with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence and then dried for use. An appropriate amount of zinc acetate was dissolved in anhydrous ethanol and stirred at 60°C for 30 minutes to obtain a uniform transparent solution with a concentration of 5 mM. Then, the cleaned stainless steel substrate was immersed in the above solution for 30 seconds and then a manual lift was used to lift the substrate at a speed of 3 cm·min. -1 The film was pulled at a speed of , and then placed in a muffle furnace at 300℃ for annealing for 10min. This step was taken 4 times in the experiment to obtain a seed layer. After that, equimolar amounts of zinc nitrate hexahydrate and hexamethylenetetramine solutions were prepared with deionized water, and the equal volumes were fully mixed to obtain a hydrothermal growth solution with a final concentration of 20mM. The stainless steel plate loaded with ZnO seed crystals was immersed in the hydrothermal growth solution, hydrothermally grown at 90℃ for 4h, washed several times with deionized water and anhydrous ethanol, and annealed at 500℃ for 30min after drying to remove organic residues, thus obtaining a stainless steel plate sample loaded with ZnO nanoarrays. Afterwards, it was immersed in disinfectant alcohol for sterilization and dried for standby use. 2) Extraction of bacteriophage endolysin (in order to better illustrate the invention, the present invention uses bacteriophage ZBSTP8 as the experimental object. The technicians in this technical field can choose different materials according to the actual situation, but the equivalent substitutions or changes made are all within the protection scope of the present invention): Use a kit to extract the DNA of bacteriophage ZBSTP8, query the genome sequence of bacteriophage ZBSTP8 from NCBI (deposit number CCTCC NO: M 2024525), and design primers according to the endolysin gene sequence. Use phage DNA as a template and primers for PCR amplification to obtain the endolysin encoding gene fragment. Use Beijing Quanshijin Biological Co., Ltd. The E1Expression Kit was used to construct the recombinant plasmid, and the recombinant plasmid was amplified by PCR and verified by sequencing. The recombinant plasmid with the correct sequencing results was transferred into E. coli BL21 (DE3) pLysS competent cells, and IPTG inducer was added to induce the expression of endolysin. The protein bands were observed by SDS-PAGE electrophoresis, and the protein was purified by Ni-NTA purification system. 3) Preparation of pH-responsive antibacterial coating: The previously prepared ZnO substrate was immersed in an ethanol solution of 3-(trimethoxymethylsilyl) methacrylate (TMSPMA) with a volume concentration of 2 vol% at room temperature for 10 h. After taking out the sample, it was placed in an oven at 80°C for 1 h to obtain a silane coupling agent-modified zinc oxide nanostructure, which was recorded as ZnO-TMSPMA. A silane coupling agent-modified zinc oxide nanostructure was obtained, which was recorded as ZnO-TMSPMA. A 1wt% ethanol solution of the photoinitiator benzophenone (BP) was prepared, and ZnO-TMSPMA was immersed in the ethanol solution of BP for 30 min and then dried in the dark. For the ZnO-BP sample, UV grafting was performed, and the aqueous solution of the monomer (i.e., CEA or PAA) was degassed with a nitrogen flow. Subsequently, the CEA monomer solution (20 μL, 5wt%) was added to the ZnO-BP sample, and the sample was covered with a quartz plate. The sandwich system was exposed to UV light (high pressure mercury lamp, 300 W, main wavelength 365 nm) for 30 min. ZnO-PCEA was activated in a 2-(N-morpholino)ethanesulfonic acid (MES) solution (pH 5.5) containing 0.4 M EDC and 0.1 M NHS at 4°C for 1 h. For the stratified brush sample, UV graft polymerization of PAA monomer on ZnO-PCEA was carried out according to the same procedure. The obtained stratified sample was denoted as ZnO-PCEA-PAA. The ZnO-PCEA-PAA sample was incubated in a 1 mg / mL Lys81 solution for 24 h. The sample was then washed and dried. The peptide-loaded sample was named ZnO-PCEA(lys)-PAA.

3. The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin according to claim 2, characterized in that: In the step 1), the stainless steel plate loaded with ZnO seed crystals is immersed in a hydrothermal growth solution and then hydrothermally grown at 90° C. for 4 hours.

4. The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin according to claim 2, characterized in that: In the step 2), the endolysin of the Salmonella phage ZBSTP8 screened independently is used as an additional bactericidal element on the nanocolumn.

5. The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin according to claim 2, characterized in that: In the step 2), primers are designed according to the endolysin gene sequence: F: 5'-ATGGCTATTAGCAAAAACATGAAGGC-3' R: 5'-TCATGCCACAACTCCGCC-3'.

6. The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin according to claim 2, characterized in that: In the step 2), the concentration of the endolysin protein solution used is 108.5 μg / ml.

7. The pH-responsive anti-adhesive and antibacterial nanocolumn coating based on bacteriophage endolysin according to claim 2, characterized in that: In the step 3), when the PAA monomer is grafted and polymerized by ultraviolet light on ZnO-PCEA, the irradiation time is 30 minutes.

Citation Information

Patent Citations

  • Preparation method of super-hydrophilic antifog and antibacterial coating without light treatment

    CN103073937A

  • Three-dimensional carrier of microarray biochip and preparation method thereof

    CN103147133A

  • Polymer brush with bacterial responsiveness and preparation method thereof

    CN111995788A

  • Method for constructing micro-nano structure with antibacterial function on surface of metal substrate

    CN114059047A

  • Food-borne pathogenic bacterium nano-enzyme lateral flow chromatography detection method based on bacteriophage recognition

    CN115128269A